Emerging Sign Languages of the Americas - Ben, Braithwaite; Brigitte, Garcia; Coppola, Marie; Emmanuella, Martinod; Ivani, Fusellier; John B., Haviland; John, Haviland; Kristian, Ali; Laura, Horton; Le Guen, Olivier; Rebeca, Petatillo; Rita, Kinil Canché; et al. (Sign Language Typology [SLT] ;, 2020)
This volume is the first to bring together researchers studying a range of different types of emerging sign languages in the Americas, and their relationship to the gestures produced in the surrounding communities of hearing individuals. Contents Acknowledgements Olivier Le Guen, Marie Coppola and Josefina SafarIntroduction: How Emerging Sign Languages in the Americas contributes to the study of linguistics and (emerging) sign languages Part I: Emerging sign languages of the Americas. Descriptions and analysis John HavilandSigns, interaction, coordination, and gaze: interactive foundations of "Z"--an emerging (sign) language from Chiapas, Mexico Laura HortonRepresentational strategies in shared homesign systems from Nebaj, Guatemala Josefina Safar and Rodrigo Petatillo ChanStrategies of noun-verb distinction in Yucatec Maya Sign Languages Emmanuella Martinod, Brigitte Garcia and Ivani FusellierA typological perspective on the meaningful handshapes in the emerging sign languages on Marajó Island (Brazil) Ben BraithwaiteEmerging sign languages in the Caribbean Olivier Le Guen, Rebeca Petatillo and Rita (Rossy) Kinil CanchéYucatec Maya multimodal interaction as the basis for Yucatec Maya Sign Language Marie CoppolaGestures, homesign, sign language: Cultural and social factors driving lexical conventionalization Part II: Sociolinguistic sketches John B. HavilandZinacantec family homesign (or "Z") Laura HortonA sociolinguistic sketch of deaf individuals and families from Nebaj, Guatemala Josefina Safar and Olivier Le GuenYucatec Maya Sign Language(s): A sociolinguistic overview Emmanuella Martinod, Brigitte Garcia and Ivani FusellierSign Languages on Marajó Island (Brazil) Ben BraithwaiteSociolinguistic sketch of Providence Island Sign Language Kristian Ali and Ben BraithwaiteBay Islands Sign Language: A Sociolinguistic Sketch Marie CoppolaSociolinguistic sketch: Nicaraguan Sign Language and Homesign Systems in Nicaragua.